PENGELOLAAN PELAYANAN KESEHATAN DENGAN PENDEKATAN MANAJEMEN KASUS DI PANTI WERDHA BUDI LUHUR JAMBI - Faridah Faridah (Jurnal Akademika Baiturrahim Jambi, 2018)
Case management ini one of the methods to deal with the problems that occur in the elderly. PSTW Budi Luhur jambi is a social body that cares about the elderly problem by providing health service facilities.This research is a qualitative approach. The technique used by the researcher to select the informant is purposive sampling technique, where the informant is chosen based on certain consideration and considered as the right person in giving yhe information according to the need of the informant.The result of case management reseach that is applied in PSTW Budi Luhur Jambi is very diverse starting from health problems, social problems and spirituality of  elderly people. The activities undertaken with group guidance, conseling conducted by competent and counseling  can be done by students who do clinical practice in PSTW Budi Luhur jambi with guidance officer lecturer supervisor. The case management phase ini PSTW Budi Luhur Jambi on the elderly problem start from assesment, implementation, controling, advication and termination